Effects of Combined Early In-Patient Cardiac Rehabilitation and Structured Home-based Program on Function among Patients with Congestive Heart Failure: A Randomized Controlled Trial - Babu, Abraham Samuel (Medknow Publications & Media Pvt Ltd, 2011)
AIMS: To determine the effects of combined in-patient rehabilitation with a home-based program on function and quality of life. SETTING AND DESIGN: Tertiary care, university teaching hospital, randomized controlled trial. PATIENTS AND METHODS: Thirty admitted patients with congestive heart failure with New York Heart Association class II -IV. A five step individualised phase-1 cardiac rehabilitation program followed by a structured home based rehabilitation for eight weeks was given to the experimental group while the control group only received physician directed advice. Six minute walk distance was assessed at discharge and follow-up, while quality of life (SF36) was assessed at admission, discharge, and follow-up. STATISTICAL ANALYSIS USED: Independent t-test, paired t-test and repeated measures ANOVA with Bonferroni post-hoc analysis. RESULTS: At admission patients in both the groups were comparable. After the phase-1 cardiac rehabilitation, there was a change in the six minute walk distance between control and experimental group (310 m vs. 357 m, respectively; P = 0.001). Following the eight week home-based program, there was a greater increase in six minute walk distance in the experimental group when compared to the control group (514 m vs. 429 m; P < 0.001). Quality of life as measured by the SF-36 at the end of 8-weeks showed a statistically significant difference (P < 0.05) in the experimental group for both the mental and physical components. CONCLUSION: Early in-patient rehabilitation followed by an eight week home based exercise program improves function and quality of life in patients with congestive heart failure.